Provision of dietary advice for people with an ileostomy: a survey in the UK and Ireland. (9th August 2020) - Mitchell, A.; England, C.; Atkinson, C.
Abstract: Aim: The aim was to explore whether people with an ileostomy in the UK and Ireland receive the dietary advice they require. Method: An online survey with multiple‐choice questions asked people with an ileostomy about the dietary advice they received and would have preferred to receive. Participants were recruited via websites of the Ileostomy and Internal Pouch Association and Crohn's and Colitis UK and via social media. People with a current ileostomy, age 16 years or over, and living in the UK or Ireland were eligible for inclusion. Responses were analysed using descriptive statistics. Results: In all, 291 eligible responses were received and included in the analysis; 201 (69%) received advice on diet for their ileostomy from a healthcare professional or the internet. Of the 90 who did not receive dietary advice, 82 (91%) would have liked advice. Stoma nurses were the most common source of dietary advice (55%), but many other sources were frequently reported. Most (62%) felt that at least some dietary advice they received was conflicting. Over half (55%) felt anxious about managing their diet with a new ileostomy, 39% were confused, and 31% frustrated. Of 291 respondents, 29% received advice from a dietitian compared to 60% who would have preferred advice from a dietitian. Conclusion: Many people undergoing ileostomy surgery do not receive the dietary advice and support they require. Healthcare professionals working with people with an ileostomy should be mindful they are often anxious about their diet and require clear and consistent dietary advice and support.